KONSEP KETUHANAN DI DALAM AGAMA TAOISME DAN KONFUSIANISME (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2021)
There are many writings that say that Taoism and Confucianism are not a religion, because it places more emphasis on human morals both for fellow human beings and with nature. However, the author considers Taoism and Confucianism as religions, because both have the concept of divinity, scriptures, personal ordinances and a view of life after death. This type of research uses library research. Data collection in this study was used in the form of literature, namely looking for literature sources regarding the discussion. Discussion analysis using a descriptive method. The results of the discussion are Taoism and Confucianism are religions that want to make humans wise and get eternal happiness by merging with Tao or Tien (God). In Taoism, the Tao cannot be seen and heard, but it can be felt and is everywhere. Everything originates from the Tao and returns to it. Whereas in Confucian terms God is referred to as Tien. Tien is the source, regulator, and destination of all things.